Experimental Study on Oxygen-Enriched Sintering of Vanadium-Titanium Magnetite - Hao Liu; Yuelin Qin; Xinlong Wu; Bing Xie (Journal of Chemistry)
The influences of various factors, such as oxygen enrichment time, oxygen enrichment load, and ignition temperature, on the technical indices and sintering performance in the vanadium-titanium magnetite sintering process are simulated using sinter pot experiments. The experiments are based on the field production parameters of a sintering trolley in a steel enterprise in southwest China. Prolonged oxygen enrichment time results in the gradual increase in vertical sintering speed, sintering utilization coefficient, sintered ore yield, sintered ore drum strength, and reductivity. However, the low-temperature reduction pulverability of the sintered ore deteriorates. Oxygen enrichment load increases from 0 m3/h to 2.9 m3/h, and yield increases by 1.1%, while the vertical sintering speed and utilization coefficient increase slightly. Sintered ore drum strength increases from 65.33% to 68.00%, antiwear index decreases to 0.47%, and low-temperature reduction pulverability decreases from 65.07% to 62.85%. The increased ignition temperature is beneficial to improve the drum strength and yield of the ore but reduces the vertical sintering speed and utilization coefficient. With the increase in ignition temperature, the low-temperature reduction pulverability tends to increase first and then decrease. Changes in oxygen time, oxygen enrichment load, and ignition temperature have no significant effects on the soft melting performance of the sintered ore.